Exploring the risks to identity security and privacy in cyberspace - Nurse, J (Association for Computing Machinery, 2015)
Cyberspace, a world of great promise, but also, of great peril. Pirates, predators, and hackers galore, are you and your online identity at risk in this wild frontier?